[RETRACTED ARTICLE] Long non-coding RNA-ROR aggravates myocardial ischemia/reperfusion injury - Zhang,Weiwei (2018)
Long non-coding RNAs (lncRNAs) play an important role in the pathogenesis of cardiovascular diseases, especially in myocardial infarction and ischemia/reperfusion (I/R). However, the underlying molecular mechanism remains unclear. In this study, we determined the role and the possible underlying molecular mechanism of lncRNA-ROR in myocardial I/R injury. H9c2 cells and human cardiomyocytes (HCM) were subjected to either hypoxia/reoxygenation (H/R), I/R or normal conditions (normoxia). The expression levels of lncRNA-ROR were detected in serum of myocardial I/R injury patients, H9c2 cells, and HCM by qRT-PCR. Then, levels of lactate dehydrogenase (LDH), malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione peroxidase (GSH-PX) were measured by kits. Cell viability, apoptosis, apoptosis-associated factors, and p38/MAPK pathway were examined by MTT, flow cytometry, and western blot assays. Furthermore, reactive oxygen species (ROS) production was determined by H2DCF-DA and MitoSOX Red probes with flow cytometry. NADPH oxidase activity and NOX2 protein levels were measured by lucigenin chemiluminescence and western blot. Results showed that lncRNA-ROR expression was increased in I/R patients and in H/R treatment of H9c2 cells and HCM. Moreover, lncRNA-ROR significantly promoted H/R-induced myocardial injury via stimulating release of LDH, MDA, SOD, and GSH-PX. Furthermore, lncRNA-ROR decreased cell viability, increased apoptosis, and regulated expression of apoptosis-associated factors. Additionally, lncRNA-ROR increased phosphorylation of p38 and ERK1/2 expression and inhibition of p38/MAPK, and rescued lncRNA-ROR-induced cell injury in H9c2 cells and HCM. ROS production, NADPH oxidase activity, and NOX2 protein levels were promoted by lncRNA-ROR. These data suggested that lncRNA-ROR acted as a therapeutic agent for the treatment of myocardial I/R injury.